Recent evolutions of natural foci of leptospirosis and small mammal communities (rodentia, insectivora) in the Republic of Moldova (One Health & Risk Management, 2020)
Introduction. Leptospirosis is a zoonosis caused by microorganisms of the genus Leptospira with a global spread. The main reservoir of leptospires are the small mammals, which survive after infection, spreading the causative agent in the environment with urine.Material and methods. The studied were conducted in 2017-2019 in different ecosystems, where 1617 small mammals were collected, investigated for the presence of specific antibodies to Leptospira spp. Ecological analysis of small mammal communities was performed and leptospire-carrier species were identified.Results. 17 species of the order Rodentia and Soricomorpha were identified. The most widespread are A. sylvaticus, A. flavicollis and A. agrarius with a frequency of 100%, abundant and dominant in most of the studied ecosystems. Antibodies specific to Leptospira spp. were detected in 9 species, the highest share of the species with leptospire belongs to A. agrarius (53.85%) and C. glareolus (11.54%). The serogroups Leptospira grippotyphosa, L. icterohaemorrhagiae and L. pomona were highlighted.Conclusions. The epizootiological process in leptospirosis is maintained active in nature by 9 species of small mammals, including one of the Europe species A. agrarius, the leptospire rate was determined at 53.85%. The intense circulation of leptospires in the small mammal population determines the need to monitor the multiannual dynamics of their in order to establish changes in natural foci of leptospirosis, forecast the epizootological situation and the risk of spreading of disease among the human population.
Keywords: small mammals; Leptospira spp.; leptospirosis; ecosystem; biotope